2022
DOI: 10.1111/joss.12770
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic and antagonistic ingredient interactions as a sugar reduction strategy in chocolate milk

Abstract: Here we report synergistic and antagonistic mixture interactions between sucrose, vanillin, and cocoa powder as a potential added sugar reduction strategy in chocolate milk.Objectives of this project were to (i) model consumer perception of relevant sensory attributes as a function of sucrose, vanillin, and cocoa powder in chocolate milk, (ii) test for the presence of synergistic, additive, and antagonistic interactions via the isobole method, and (iii) determine consumer acceptance of these samples with both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
(73 reference statements)
2
5
0
Order By: Relevance
“…As expected, lower concentrations of sucrose resulted in significantly lower sweet taste intensity (p < 0.0001) and significantly higher bitter taste intensity (p < 0.0001). Previous studies working with sugar reduction in chocolate milk have found similar results [14,30]. We know that sweetness can mask bitterness, and that these two tastes are often inversely correlated [14].…”
Section: The Effect Of Sucrose Reduction On Sensory Attributesmentioning
confidence: 58%
See 3 more Smart Citations
“…As expected, lower concentrations of sucrose resulted in significantly lower sweet taste intensity (p < 0.0001) and significantly higher bitter taste intensity (p < 0.0001). Previous studies working with sugar reduction in chocolate milk have found similar results [14,30]. We know that sweetness can mask bitterness, and that these two tastes are often inversely correlated [14].…”
Section: The Effect Of Sucrose Reduction On Sensory Attributesmentioning
confidence: 58%
“…In relation to fat and sugar reduction, the enhancing properties of other modalities are very relevant. Using aromas to increase the sweetness perception or the perception of fat in foods and beverages is a well-known strategy when reducing either the fat or the NSs without changing the consumers' perception of the product [9][10][11][12][13][14][15]. Also, tastes, such as sweetness, may enhance the perception of an aroma [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An important role is played by inhibitory mechanisms responsible of antagonistic interactions among odorants [ 47 ]. Antagonistic interactions among sensorial properties and chemical compounds could also be very important in the definition of a production strategy: for example, ingredients showing bitterness suppression could be used to decrease added sugar content while preserving consumer acceptability in chocolate milk [ 48 ].…”
Section: Resultsmentioning
confidence: 99%